Dakwah Melalui Live Streaming Tiktok Pada Mobile Legends; Studi Fenomenologis Akun @Abiazkakiaa - Neng Ayu Saadah (Universitas Islam Negeri Imam Bonjol Padang, 2022)
This study aims to analyze the power of social media on the Tiktok application to convey a message of proselytizing for young people. This research uses qualitative methods. Data collection uses a virtual ethnographic method, where researchers observe activities on tiktok social media @abiazkakiaa. The results of this study found that Tiktok can actually be optimized for the purpose of conveying a proselytizing message as exemplified by ustadz Abi Azkakia. One of Tiktok's potentials is in an attractive visual display that can see the activities of mobile legend games widely and openly with the Live Streaming feature. With this feature, ustaz Abi is easier to convey the message or content of his proselytizing based on the Quran and Hadith. He focuses on conveying aqidah and morals with the language of mad'unya purpose so that it is easily accepted by generations of Tiktok users as proselytizing partners.